If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6p + -6 = -36 Reorder the terms: -6 + -6p = -36 Solving -6 + -6p = -36 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -6p = -36 + 6 Combine like terms: -6 + 6 = 0 0 + -6p = -36 + 6 -6p = -36 + 6 Combine like terms: -36 + 6 = -30 -6p = -30 Divide each side by '-6'. p = 5 Simplifying p = 5
| 8=vf-3 | | 25=5(7x)-3 | | 15(y+3)=6(y-5) | | X^2-3x-40=o | | 10(v+2)-4v=3(2v+3)-15 | | ((8/4)6)x2 | | 5a-75=-20(a+20) | | p-2=5 | | -14x+1=-55 | | 10x+40=4x-8 | | 13x-12=4(3x+4)-4 | | -45+X=-27 | | -13=k-13+14k | | 5m-5=-25 | | x-.20x=338 | | 10x+40=4x+8 | | 45+X=-27 | | 8+10k-11k=0 | | x-.20x=512 | | (-30(-17))-(210(-3))= | | -36=-11n+8n | | 6y-60=42 | | 12=x-(-11) | | -36=k-13+14k | | 13p+6=32 | | sin^-1(3.2/4) | | 34=x+9+12 | | 11m+8=19 | | 0.3x-0.6=0.2x+7 | | -n-7=-16 | | 0=-13b+13b | | 9y^4+12y^2+1=0 |